2018
DOI: 10.3390/s18051513
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Metamaterial-Based Sensor for Dielectric Characterization of Liquids

Abstract: This article proposed to build a system founded on metamaterial sensor antennas, which can be used to evaluate impurities in aqueous substances according to the quality of transmission between the sensor antennas. In order to do this, a dedicated setup with tests in several frequencies was deployed so as to monitor the behavior of transmission variation between sensors. These sensors are microstrip antennas with a ground plane of resonant cleaved metallic rings; the substrate functions as a metamaterial for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…As it can be seen in Table 1, the reported solution based on dumbbell DGS resonators offers a good sensor performance (i.e., combination of sensitivity, resolution, and input dynamic range). In references [25,26,40,41], the authors use NaCl as the solute, whereas the other sensors are used for glucose concentration measurement, except [42,43], devoted to measurement of the Zn concentration in DI water. According to Table 1, for the NaCl or glucose concentration, the proposed sensor and the one presented in [26] offer the best sensitivity and resolution, the key sensor parameters.…”
Section: Comparison With Other Microwave Sensor Approaches and Dismentioning
confidence: 99%
“…As it can be seen in Table 1, the reported solution based on dumbbell DGS resonators offers a good sensor performance (i.e., combination of sensitivity, resolution, and input dynamic range). In references [25,26,40,41], the authors use NaCl as the solute, whereas the other sensors are used for glucose concentration measurement, except [42,43], devoted to measurement of the Zn concentration in DI water. According to Table 1, for the NaCl or glucose concentration, the proposed sensor and the one presented in [26] offer the best sensitivity and resolution, the key sensor parameters.…”
Section: Comparison With Other Microwave Sensor Approaches and Dismentioning
confidence: 99%
“…Similarly, the recent development of sensors can be highlighted for several applications such as characterization of NaCL as solute in concentration in very dilute solutions [6][7][8], identification of the depth of burns in biological tissues [9], and characterization of chemical and organic materials [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature revealed that the use of sensors to determine the dielectric properties of liquid materials is realizable. Researchers have successfully employed the sensors to estimate the distance between antennas as well to determine the dielectric parameters of liquid materials [9,10]. The fabrication of chemical sensors has also been realized using microporous polymer thin films [11].…”
Section: Introductionmentioning
confidence: 99%